Peran Bimbingan dan Konseling dalam Pencapaian Tugas Perkembangan Narapidana Anak - Handayan, Puji Gusri; Hidayat, Hafiz (citeus, 2025)
Aside from school, guidance and counseling service can also be provided at the Children’s Special Guidance Institute. Guidance and counseling are essential for child prisoners as it aids them in achieving their development tasks. However, up to recently, child prisoners have not had maximum access to guidance and counseling services due to limited human resources. This study used literature studies and documentary methods involving scientific articles, laws, books, or other works and studies related to the position of child prisoners in criminal cases.